Investigating the Impact of Collaborative Learning on Arabic Language Achievement of Grade IX Students at MTsN 3 Palu - Maharani, Puan; Ubadah; Zul Aini Rengur (Albariq: Jurnal Pendidikan Bahasa Arab, 2025)
This study examines the effect of collaborative learning on the Arabic language learning outcomes of grade IX students at MTsN 3 Palu City. This study aims to investigate the significant effect of collaborative learning on Arabic language learning outcomes, particularly among grade IX students at MTsN 3 Palu City. This study uses a quantitative approach with data collection techniques including observation, questionnaires, and tests. The total population for this study is 100 people. Sampling was carried out using the Slovin formula, leading to a total sample size of 29 people. Data analysis was conducted using a simple linear regression test with the help of SPSS version 25. The results of this study indicate that collaborative learning has a significant effect on the Arabic language learning outcomes of grade IX students at MTsN 3 Palu City. The coefficient of determination for the collaborative learning variable on Arabic language learning outcomes is 0.856 or 85.6%, and the remaining 14.4% is influenced by other factors that are not studied in this research. The significance value is at 0.000, where 0.000 > 0.05, indicating that collaborative learning significantly affects Arabic language learning outcomes. Based on the results of this study, the implications for educational institutions are positive, and teachers are expected to apply the collaborative learning method in instruction and provide support to achieve effective learning outcomes aligned with the desired goals. Arabic language learning, collaborative learning method, Arabic language learning outcomes.